Initial multicentre experience of 68gallium‐PSMA PET/CT guided robot‐assisted salvage lymphadenectomy: acceptable safety profile but oncological benefit appears limited. (20th June 2017) - Siriwardana, Amila; Thompson, James; van Leeuwen, Pim J.; Doig, Shaela; Kalsbeek, Anton; Emmett, Louise; Delprado, Warick; Wong, David; Samaratunga, Hemamali; Haynes, Anne‐Maree; Coughlin, Geoff; Stricker, Phillip
Abstract : Objectives: To evaluate the safety and short‐term oncological outcomes of 68 gallium‐labelled prostate‐specific membrane antigen ( 68 Ga‐PSMA) positron‐emission tomography (PET)/computed tomography (CT)‐directed robot‐assisted salvage node dissection (RASND) for prostate cancer oligometastatic nodal recurrence. Materials and Methods: Between February 2014 and April 2016, 35 patients across two centres underwent RASND for 68 Ga‐PSMA PET/CT‐detected oligometastatic nodal recurrence. RASND was performed using targeted pelvic dissection, unilateral extended pelvic template or bilateral extended pelvic template dissection, depending on previous pelvic treatment and extent/location of nodal disease. Complications were reported using the Clavien–Dindo classification system. Definitions of prostate‐specific antigen (PSA) treatment response to RASND were defined as 6‐week PSA <0.2 ng/mL (broad definition) or PSA <0.05 ng/mL (strict definition) in those who had undergone primary prostatectomy, and 6‐week PSA level < post‐radiotherapy nadir in those who had undergone primary radiotherapy. Biochemical recurrence (BCR) after RASND was defined as a PSA >0.2 ng/mL or PSA > nadir, for those who had undergone primary prostatectomy and primary radiotherapy, respectively. Predictors of treatment response were analysed using univariate binary logistic regression. Results: A total of 58 lesions suspicious for lymph node metastases (LNM) in 35 patients were detected on 68 Ga‐PSMA imaging. A total of 32 patients (91%) had histopathologically proven LNM at RASND, with a total of 87 LNM and a median (interquartile range) of 2 (1–3) LNM per patient. In all, eight patients (23%) experienced complications, all Clavien–Dindo grade ≤2. Treatment response was seen in 15 (43%) and 11 patients (31%), using the broad and strict definitions, respectively. BCR‐free survival and clinical recurrence‐free survival at a median follow‐up of 12 months were 23% and 66%, respectively, for the entire cohort. Bilateral template dissection was the only significant univariate predictor of treatment response in our cohort. Conclusions: Although RASND appears safe and feasible, less than half of our cohort had a treatment response, and less than a quarter experienced BCR‐free survival at 12‐month median follow‐up. 68 Ga‐PSMA imaging underestimates micro‐metastatic disease, therefore RASND will rarely be curative. Strict patient selection and restricting RASND to clinical trials is recommended. Long‐term follow‐up from such trials is required to further assess potential quality of life and mortality benefits.